Актуалізація методологічної функції загальнотеоретичної юриспруденції - Оборо́тов, Ю́рій Микола́йович; Оборотов, Юрий Николаевич; Oborotov, Jurij (Одеса : Юрид. л-ра, 2012)
The article describes the characteristics of the methodological function of general theoretical jurisprudence. Author shows the connection of the general theoretical jurisprudence and legal philosophy in the aspect of translation of methodological tools in the legal sphere. Article deals with the main ways of the methodological function of general theoretical jurisprudence implementation such as: development of the language of law, the formation of the legal style and legal thinking, drawing legal categorical apparatus, juridization approaches and methods. The methodological function of the general theoretical jurisprudence is considered as actual either at the level of legal science or at the level of legal reality.
Оборотов Ю. М. Актуалізація методологічної функції загальнотеоретичної юриспруденції / Ю. М. Оборотов // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 99-105.
Keywords: юридична наука; юриспруденція; філософія права; загальнотеоретична юриспруденція; функції загальнотеоретичної юриспруденції; теорія та практика юридичної діяльності; science of law; jurisprudence; legal philosophy; general theoretical jurisprudence; functions of general theoretical jurisprudence; theory and practice of legal activity